Ceramic shell back layer slurry with good fluidity and preparation method thereof

By adding a three -level spherical sand to the ceramic shell back layer slurry, the problem of accumulation of back layer slurry at the inner concave structure is solved, and the macro thickness of the macro thickness of the ceramic shell is evenly distributed by the internal micro component, which improves, improved, and improves the internal micro component, which improves the uniform distribution of internal micro components, and improves the internal micro component. A single crystal integrity qualification rate of single crystal blades.

CN119038977BActive Publication Date: 2025-01-21AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411545555.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-21
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing ceramic shell back layer slurry is prone to accumulate in the concave structure, resulting in inconsistent thickness uniformity and the inability to effectively improve the uniformity of the refractory powder distribution of the internal microscopic components.

Method used

By adding a three -level trace spherical sand to the powder tolerance powder, prepare the back layer powder, and mix it with the silica solution, wetting agent, removing agent and other substances to form a good liquid ceramic shell back layer Purch.

Benefits of technology

Improve the liquidity and uniformity of ceramic shell back layer slurry, improve the macro thickness and uniformity of ceramic shells, and improve the uniform distribution of refractory materials for the internal micro component, providing a more even directional solidarity temperature The field improves the single crystal integrity qualification rate of single crystal blades.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038977B_ABST
    Figure CN119038977B_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic shell back layer slurry with good fluidity and a preparation method thereof. The mass percentages of various substances in the back layer slurry are as follows: 65-87wt% of back layer powder, 12-34wt% of silica sol, 0.2-0.8wt% of wetting agent and 0.2-0.8wt% of defoaming agent; the mass percentages of various substances in the back layer powder are as follows: 97-98.5wt% of refractory powder, 0.3-1.5wt% of primary spherical sand, 0.4-0.8wt% of secondary spherical sand and 0.3-0.8wt% of tertiary spherical sand. The method comprises the following steps: placing primary spherical sand, secondary spherical sand and tertiary spherical sand in a roasting furnace for roasting; placing refractory powder, primary spherical sand, secondary spherical sand and tertiary spherical sand in a V-type mixer for mixing to obtain a back layer powder; adding silica sol, a wetting agent and a defoaming agent to a slurry mixing barrel in sequence for stirring; adding the back layer powder to the slurry mixing barrel for continuous stirring to obtain a ceramic shell back layer slurry with good fluidity. The present invention can improve the uniformity of the macroscopic thickness of the ceramic shell and improve the uniform distribution of the refractory powder of the internal microscopic components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic shell back layer slurry preparation, and in particular relates to a ceramic shell back layer slurry with good fluidity and a preparation method thereof. Background Art

[0002] As we all know, the turbine blades for aircraft engines are known as the jewel in the crown of modern industry. The materials of turbine blades have evolved from the initial equiaxed crystal casting high-temperature alloy to the directional solidification columnar crystal high-temperature alloy, and now to the single crystal high-temperature alloy. Single crystal high-temperature alloy turbine blades are made by precision casting, which has many preparation steps and a long preparation process. The ceramic shell is used as a container for the directional solidification of single crystal high-temperature alloy turbine blades. During the directional solidification process of the single crystal blades, the ceramic shell acts as a medium for heat transfer, and its thickness uniformity has an important influence on the directional solidification temperature field of the single crystal blades.

[0003] The ceramic shell is a multi-layer composite material, each layer of which is composed of slurry and sand, that is, each layer of material includes a layer of slurry and a layer of sand. The surface slurry is the key factor affecting the quality of the inner surface of the ceramic shell, and a large amount of (that is, multiple layers) back layer slurry is the key factor affecting the thickness uniformity of the ceramic shell. Since the preparation process of the ceramic shell is a traditional coating process, the back layer slurry shows different coating thicknesses at different structures of the ceramic shell. Generally, the thickness at the flat surface is moderate, the thickness of the protruding structure is small, and the thickness of the concave structure is large due to the accumulation of the back layer slurry. In order to solve the problem of inconsistent thickness uniformity of the ceramic shell, the most effective measure is to improve the fluidity of the back layer slurry of the ceramic shell, thereby reducing the accumulation of the back layer slurry at the concave structure and improving the thickness uniformity of the ceramic shell.

[0004] The back layer slurry of the ceramic shell is composed of refractory powder, silica sol, wetting agent, defoaming agent and other substances. The existing technology usually adopts methods such as adding a modifier to the silica sol to modify it, adjusting the type and / or ratio of the wetting agent, etc. to change the rheological properties of the back layer slurry of the ceramic shell, increase the wetting angle between the back layer slurry and the wax mold / shell, and thus improve the fluidity of the back layer slurry of the ceramic shell. This method of improving the fluidity of the back layer slurry only regulates the fluidity of the silica sol itself, and has no obvious change on the refractory powder itself. The wetting agent and other additives disappear after roasting, and what remains is still the gelled product of the refractory powder and the silica sol, and the combination of the two themselves is not changed. The final performance is that the thickness uniformity of the ceramic shell is improved on a macroscopic level, but the distribution of the refractory powder of the microscopic components inside the ceramic shell is not improved. Therefore, there is an urgent need to develop a ceramic shell back layer slurry with good fluidity and a preparation method thereof, so as to achieve the effect of improving the uniformity of the macroscopic thickness of the ceramic shell and improving the uniform distribution of the refractory material powder of the microscopic components inside the ceramic shell.

[0005] The invention patent with application publication number CN117303893A discloses a high-stability ceramic shell back layer slurry and its preparation method, in which the refractory powder accounts for 60-75wt%, the binder accounts for 25-30wt%, the defoamer accounts for 0.3-0.5wt%, the wetting agent accounts for 0.3-0.5wt%, and the nanofiber accounts for 4-10wt%. The method is: prepare nanofibers by electrostatic spinning process; add the binder, defoamer and wetting agent to the slurry mixing barrel in sequence and stir, then add part of the nanofibers and part of the refractory powder to the slurry mixing barrel and stir; increase the stirring speed, add the remaining part of the nanofibers and the remaining part of the refractory powder to the slurry mixing barrel and stir.

[0006] The invention patent with application publication number CN118385441A discloses a polymer modified ceramic shell material and a preparation method thereof, wherein the surface layer material comprises a first modified polymer, a first silica sol binder, silicon powder, a first defoamer, and a first wetting agent, and the ratio of the mass of silicon powder to the remaining raw materials is (3-4):1; the back layer material comprises a second modified polymer, a second silica sol binder, silicon powder, fused white corundum powder, a second defoamer, and a second wetting agent, and the ratio of the total mass of silicon powder and fused white corundum powder to the remaining raw materials is (2.5-3.5):1. The method is: prepare the surface layer material, weigh the first silica sol binder, the first defoamer, and the first wetting agent in proportion, stir them in a reactor, add the first modified polymer and stir, and then add silicon powder and stir; prepare the back layer material, weigh the second silica sol binder, the second defoamer, and the second wetting agent in proportion, stir them in a reactor, add the second modified polymer and stir, and then add silicon powder and fused white corundum powder and stir. Although the above two technical solutions can improve the uniformity of back layer slurry coating, they can only improve the thickness uniformity of the ceramic shell on a macro scale, and cannot improve the uniformity of refractory powder distribution of microscopic components inside the ceramic shell. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a ceramic mold shell back layer slurry with good fluidity, the mass percentage of each substance in the ceramic mold shell back layer slurry is 65-87wt% of back layer powder, 12-34wt% of silica sol, 0.2-0.8wt% of wetting agent, and 0.2-0.8wt% of defoaming agent; the mass percentage of each substance in the back layer powder is 97-98.5wt% of refractory material powder, 0.3-1.5wt% of primary spherical sand, 0.4-0.8wt% of secondary spherical sand, and 0.3-0.8wt% of tertiary spherical sand.

[0008] Preferably, the refractory powder is any one of mullite powder, zircon powder and alumina powder, and the particle size of the refractory powder is 200-325 mesh.

[0009] In any of the above schemes, it is preferred that, according to the material type of the refractory powder used in the ceramic shell back layer slurry, spherical sand with the same chemical composition is selected, that is, the materials of the first-level spherical sand, the second-level spherical sand and the third-level spherical sand are the same as the material of the refractory powder; the particle size of the first-level spherical sand is 100-120 mesh, the particle size of the second-level spherical sand is 120-140 mesh, and the particle size of the third-level spherical sand is 140-150 mesh; the sphericity values ​​of the first-level spherical sand, the second-level spherical sand and the third-level spherical sand are not less than 0.95.

[0010] In any of the above schemes, it is preferred that the wetting agent is a fatty phosphate and / or a fatty alcohol polyoxyethylene ether; the defoamer is any one of n-octanol, polydimethylsiloxane, and a polyether defoamer. The polyether defoamer is a GP type, which can be obtained by preparing polymerized propylene oxide and ethylene oxide or by preparing propylene oxide and glycerol.

[0011] In any of the above schemes, preferably, the ceramic shell back layer slurry includes mullite powder back layer slurry, zircon powder back layer slurry, and alumina powder back layer slurry.

[0012] The mass percentage of each substance in the mullite powder back layer slurry is 68-77wt% for the back layer powder, 22-31wt% for the silica sol, 0.3-0.6wt% for the wetting agent, and 0.3-0.6wt% for the defoaming agent; the mass percentage of each substance in the back layer powder is 97.8wt% for the mullite powder, 1.2wt% for the primary spherical mullite sand, 0.6wt% for the secondary spherical mullite sand, and 0.4wt% for the tertiary spherical mullite sand; the particle sizes of the mullite powder, the primary spherical mullite sand, the secondary spherical mullite sand, and the tertiary spherical mullite sand are 200 mesh, 100 mesh, 120 mesh, and 150 mesh, respectively.

[0013] The mass percentages of various substances in the zircon powder back layer slurry are as follows: 75-84wt% of the back layer powder, 15-24wt% of the silica sol, 0.2-0.5wt% of the wetting agent, and 0.2-0.5wt% of the defoaming agent; the mass percentages of various substances in the back layer powder are as follows: 98.4wt% of zircon powder, 0.4wt% of the primary spherical zircon sand, 0.6wt% of the secondary spherical zircon sand, and 0.6wt% of the tertiary spherical zircon sand; the particle sizes of the zircon powder, the primary spherical zircon sand, the secondary spherical zircon sand, and the tertiary spherical zircon sand are 200 mesh, 120 mesh, 140 mesh, and 150 mesh, respectively.

[0014] The mass percentage of each substance in the alumina powder back layer slurry is 72-79wt% for the back layer powder, 20-27wt% for the silica sol, 0.2-0.5wt% for the wetting agent, and 0.2-0.5wt% for the defoaming agent; the mass percentage of each substance in the back layer powder is 97.9wt% for the alumina powder, 1.0wt% for the primary spherical alumina sand, 0.5wt% for the secondary spherical alumina sand, and 0.6wt% for the tertiary spherical alumina sand; the particle sizes of the alumina powder, the primary spherical alumina sand, the secondary spherical alumina sand, and the tertiary spherical alumina sand are 325 mesh, 100 mesh, 120 mesh, and 140 mesh, respectively.

[0015] In any of the above schemes, it is preferred that the primary spherical zircon sand, the secondary spherical zircon sand and the tertiary spherical zircon sand are prepared by a calcination process, and the calcination temperature is not lower than 1200°C; the primary spherical mullite sand, the secondary spherical mullite sand and the tertiary spherical mullite sand are prepared by a high-temperature melting granulation process, and the melting temperature is not lower than 2000°C; the primary spherical alumina sand, the secondary spherical alumina sand and the tertiary spherical alumina sand are prepared by a high-temperature melting granulation process, and the melting temperature is not lower than 2000°C.

[0016] The present invention also provides a method for preparing a ceramic shell back layer slurry with good fluidity, which is used to prepare any of the above-mentioned ceramic shell back layer slurry with good fluidity, and comprises the following steps in order:

[0017] Step 1: according to the designed raw material ratio, weigh refractory powder, first-grade spherical sand, second-grade spherical sand, third-grade spherical sand, silica sol, wetting agent and defoaming agent for use;

[0018] Step 2: Put the first-level spherical sand, the second-level spherical sand and the third-level spherical sand into a refractory mortar and mix them evenly, then put the refractory mortar containing the first-level spherical sand, the second-level spherical sand and the third-level spherical sand into a roasting furnace for roasting, and cool the roasted first-level spherical sand, the second-level spherical sand and the third-level spherical sand for standby use;

[0019] Step 3: Put the refractory powder and the cooled first-grade spherical sand, second-grade spherical sand and third-grade spherical sand into a V-type mixer for mixing, and after the mixing is completed, the back layer powder is obtained;

[0020] Step 4: Add silica sol, wetting agent and defoaming agent into the slurry mixing barrel in sequence, and start the agitator for stirring at the same time;

[0021] Step 5: While keeping the agitator in the started state and without changing the stirring speed, add the obtained back layer powder into the slurry mixing barrel and continue to stir; after all the back layer powder is added, turn on the circulation cooling system of the slurry mixing barrel, and increase the stirring speed to continue stirring. After the stirring is completed, a ceramic shell back layer slurry with good fluidity is obtained.

[0022] Preferably, in step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 650-800°C, the roasting time is 2-4h, and the sand is cooled with the furnace after roasting. During the roasting and furnace cooling process, the oxygen content is ensured to be not less than 12%.

[0023] In any of the above schemes, preferably, in step three, the ambient temperature of the operating room is 15-25° C., the rotation speed of the mixer is 20-60 rpm, and the mixing time is 4-6 h.

[0024] In any of the above schemes, preferably, in step 4, the ambient temperature of the operating room is 15-25° C., the stirring speed is 500-1000 rpm, and the stirring time is 5-10 min.

[0025] In any of the above schemes, preferably, in step five, the ambient temperature of the operating room is 15-25° C., and after all the backing layer powder is added, the stirring speed is increased to 800-1200 rpm, and the stirring time is 2-4 hours.

[0026] In the present invention, the refractory kiln, roasting furnace, V-shaped mixer, slurry mixing barrel, etc. used are all traditional equipment, and there are no special requirements for the structure and model of the equipment. A circulating cooling system is provided in the slurry mixing barrel, and there are no special requirements for the structure and model of the circulating cooling system, as long as the circulating cooling system can keep the various substances of the ceramic shell back layer slurry at the required appropriate temperature during the entire stirring process. In addition, in the entire preparation process of the ceramic shell back layer slurry, parameters such as the ratio of each material, the order of adding each material, the stirring speed and the stirring time are very important. Only when the various ratio parameters and the process parameters work together can the expected technical effect of the present invention be achieved.

[0027] All levels of spherical zircon sand are prepared by calcining process, and the calcining temperature is not less than 1200°C; all levels of spherical mullite sand and all levels of spherical alumina sand are prepared by high-temperature melting granulation process, and the melting temperature is not less than 2000°C. The calcining process and high-temperature melting granulation process are both traditional processes, and conventional process methods, process parameters and process equipment can be used. The calcining temperature and the melting temperature are key parameters. It is necessary to ensure that the calcining temperature is not less than 1200°C and the melting temperature is not less than 2000°C to meet the use requirements of the present invention.

[0028] After obtaining the ceramic shell back layer slurry with good fluidity according to the material ratio and preparation process designed in the present invention, the viscosity of the back layer slurry is adjusted to 10-20s (Zahn 4# flow cup), and then the automatic shell making equipment is used to complete the shell slurry dipping, slurry control, sand pouring and drying processes according to the standard procedure, which are repeated 5-6 times, and the ceramic shell is obtained after dewaxing and roasting.

[0029] The ceramic shell back layer slurry with good fluidity and the preparation method thereof of the present invention have the following beneficial effects:

[0030] (1) To address the problem of poor fluidity of the back layer slurry of the ceramic shell, the present invention obtains a back layer powder by adding a trace amount of tertiary spherical sand into the refractory powder, and then mixes the back layer powder with silica sol, a wetting agent, a defoaming agent and other substances to obtain a ceramic shell back layer slurry. The ceramic shell back layer slurry obtained by this method has good fluidity.

[0031] (2) The present invention selects the third-grade spherical sand having the same chemical composition as the type of the ceramic shell refractory powder, and adds different contents of the third-grade spherical sand according to the demand for fluidity improvement. The operation is simple and convenient, and the fluidity improvement effect is significant.

[0032] (3) The present invention adds sand with good third-level sphericity when preparing the ceramic shell back layer slurry, which can greatly improve the fluidity and uniformity of the refractory powder itself in the ceramic shell back layer slurry, not only improving the macroscopic thickness uniformity of the ceramic shell, but also improving the uniform distribution of the refractory powder of the microscopic components inside the ceramic shell, providing a more uniform directional solidification temperature field for the ceramic shell for single crystal blades, and improving the single crystal integrity qualified rate of single crystal blades. (4) The present invention can improve the powder-liquid ratio of the ceramic shell back layer slurry by adding a trace amount of spherical sand, significantly increase the fluidity of the back layer slurry, reduce the back layer slurry pile-up during the coating process, improve the uniformity and consistency of the overall thickness of the ceramic shell, and use the improved ceramic shell to cast single crystal blades, which can effectively improve the single crystal integrity qualified rate of the casting. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A flow chart of a preferred embodiment of a ceramic shell back layer slurry with good fluidity and a preparation method thereof according to the present invention;

[0034] Figure 2 for Figure 1 The macroscopic thickness photograph of the ceramic shell prepared in the embodiment shown;

[0035] Figure 3 for Figure 1 The microstructure photos of the ceramic shell prepared in the embodiment shown;

[0036] Figure 4 This is a macroscopic thickness photograph of the ceramic shell prepared in the comparative example;

[0037] Figure 5 This is a photo of the internal microstructure of the ceramic shell prepared in the comparative example. DETAILED DESCRIPTION

[0038] In order to further understand the content of the present invention, the present invention will be described in detail below in conjunction with specific embodiments.

[0039] Embodiment 1:

[0040] According to a preferred embodiment of the ceramic shell back layer slurry with good fluidity of the present invention, the ceramic shell back layer slurry is a mullite powder back layer slurry, and the mass percentage of each substance in the mullite powder back layer slurry is 73wt% of the back layer powder, 26wt% of the silica sol, 0.5wt% of the wetting agent, and 0.5wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 97.8wt% of the back layer powder, 1.2wt% of the first-level spherical mullite sand, 0.6wt% of the second-level spherical mullite sand, and 0.4wt% of the third-level spherical mullite sand. The particle sizes of the mullite powder, the first-level spherical mullite sand, the second-level spherical mullite sand, and the third-level spherical mullite sand are 200 mesh, 100 mesh, 120 mesh, and 150 mesh, respectively. The wetting agent is fatty alcohol polyoxyethylene ether; and the defoaming agent is n-octanol.

[0041] The primary spherical zircon sand, the secondary spherical zircon sand and the tertiary spherical zircon sand are prepared by a calcination process, and the calcination temperature is not lower than 1200°C; the primary spherical mullite sand, the secondary spherical mullite sand and the tertiary spherical mullite sand are prepared by a high-temperature melting granulation process, and the melting temperature is not lower than 2000°C; the primary spherical alumina sand, the secondary spherical alumina sand and the tertiary spherical alumina sand are prepared by a high-temperature melting granulation process, and the melting temperature is not lower than 2000°C.

[0042] like Figure 1 As shown, this embodiment also provides a method for preparing a ceramic shell back layer slurry with good fluidity, which is used to prepare the ceramic shell back layer slurry with good fluidity, and includes the following steps in order:

[0043] Step 1: according to the designed raw material ratio, weigh refractory powder, first-grade spherical sand, second-grade spherical sand, third-grade spherical sand, silica sol, wetting agent and defoaming agent for use;

[0044] Step 2: Put the first-level spherical sand, the second-level spherical sand and the third-level spherical sand into a refractory mortar and mix them evenly, then put the refractory mortar containing the first-level spherical sand, the second-level spherical sand and the third-level spherical sand into a roasting furnace for roasting, and cool the roasted first-level spherical sand, the second-level spherical sand and the third-level spherical sand for standby use;

[0045] Step 3: Put the refractory powder and the cooled first-grade spherical sand, second-grade spherical sand and third-grade spherical sand into a V-type mixer for mixing, and after the mixing is completed, the back layer powder is obtained;

[0046] Step 4: Add silica sol, wetting agent and defoaming agent into the slurry mixing barrel in sequence, and start the agitator for stirring at the same time;

[0047] Step 5: While keeping the agitator in the started state and without changing the stirring speed, add the obtained back layer powder into the slurry mixing barrel and continue to stir; after all the back layer powder is added, turn on the circulation cooling system of the slurry mixing barrel, and increase the stirring speed to continue stirring. After the stirring is completed, a ceramic shell back layer slurry with good fluidity is obtained.

[0048] In step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 720°C, and the roasting time is 3 hours. After the roasting is completed, it is cooled with the furnace. During the roasting and cooling process, the oxygen content is ensured to be not less than 12%. In step 3, the ambient temperature of the operating room is 20°C, the speed of the mixer is 40rpm, and the mixing time is 5h. In step 4, the ambient temperature of the operating room is 20°C, the stirring speed is 800rpm, and the stirring time is 8min. In step 5, the ambient temperature of the operating room is 20°C. After all the back layer powder is added, the stirring speed is increased to 1000rpm, and the stirring time is 3h.

[0049] In this embodiment, spherical sand with the same chemical composition as the refractory powder used in the ceramic shell back layer slurry is selected, that is, the materials of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand are the same as the material of the refractory powder; the sphericity values ​​of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand are not less than 0.95.

[0050] The refractory kiln, roasting furnace, V-shaped mixer, slurry mixing barrel, etc. used in this embodiment are all traditional equipment, and there are no special requirements for the structure and model of the equipment. A circulating cooling system is provided in the slurry mixing barrel, and there are no special requirements for the structure and model of the circulating cooling system, as long as the circulating cooling system can keep the various substances of the ceramic shell back layer slurry at the required appropriate temperature during the entire stirring process. In addition, in the entire preparation process of the ceramic shell back layer slurry, parameters such as the ratio of each material, the order of adding each material, the stirring speed and the stirring time are very important. Only when the various ratio parameters and process parameters work together can the technical effect expected by this embodiment be achieved.

[0051] In this embodiment, various levels of spherical zircon sand are prepared by calcining process, and various levels of spherical mullite sand and various levels of spherical alumina sand are prepared by high-temperature melting granulation process. Both calcining process and high-temperature melting granulation process are traditional processes, and conventional process methods, process parameters and process equipment can be used. Calcination temperature and melting temperature are key parameters. It is necessary to ensure that the calcination temperature is not less than 1200°C and the melting temperature is not less than 2000°C to meet the use requirements of this embodiment.

[0052] After obtaining the ceramic shell back layer slurry with good fluidity according to the material ratio and preparation process designed in this embodiment, the viscosity of the back layer slurry is adjusted to 10-20s (Zahn 4# flow cup), and then the automatic shell making equipment is used to complete the shell slurry dipping, slurry control, sand pouring, and drying processes according to standard procedures, which are repeated 5-6 times. After dewaxing and roasting, the ceramic shell is obtained.

[0053] The backing slurry of this embodiment is used to prepare a ceramic shell. The macroscopic thickness of the ceramic shell is as follows: Figure 2 As shown in Figure 2, the internal microstructure of the ceramic shell is as follows: Figure 3 As shown. The standard flow area based on optical detection is 3126mm 2 The thickness of the concave part of the ceramic shell is 6.8mm, the thickness of the flat part is 5.2mm, the thickness uniformity index is 1.31, and all fluidity indicators have been improved to varying degrees. Scanning electron microscopy shows that the spherical sand in the back layer slurry has better roundness and more uniform structure.

[0054] The ceramic shell back layer slurry with good fluidity and the preparation method thereof of this embodiment have the following beneficial effects: (1) The back layer powder is obtained by adding a small amount of third-grade spherical sand to the refractory powder, and then the back layer powder is mixed with silica sol, a wetting agent, a defoaming agent and other substances to obtain the ceramic shell back layer slurry. The ceramic shell back layer slurry obtained by this method has good fluidity. (2) When preparing the ceramic shell back layer slurry, the third-grade sand with good sphericity is added, which can greatly improve the fluidity and uniformity of the refractory powder itself in the ceramic shell back layer slurry, which can not only improve the macroscopic thickness uniformity of the ceramic shell, but also improve the uniform distribution of the refractory powder of the microscopic components inside the ceramic shell, providing a more uniform directional solidification temperature field for the ceramic shell for single crystal blades, and improving the single crystal integrity qualified rate of single crystal blades.

[0055] Embodiment 2:

[0056] According to another preferred embodiment of the ceramic shell backing layer slurry with good fluidity and the preparation method thereof of the present invention, the material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0057] The ceramic shell back layer slurry is a mullite powder back layer slurry, and the mass percentage of each substance in the mullite powder back layer slurry is 68wt% of the back layer powder, 31wt% of silica sol, 0.4wt% of the wetting agent, and 0.6wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 97.8wt% of mullite powder, 1.2wt% of primary spherical mullite sand, 0.6wt% of secondary spherical mullite sand, and 0.4wt% of tertiary spherical mullite sand. The particle sizes of the mullite powder, the primary spherical mullite sand, the secondary spherical mullite sand, and the tertiary spherical mullite sand are 200 mesh, 100 mesh, 120 mesh, and 150 mesh, respectively. The wetting agent is fatty alcohol polyoxyethylene ether; and the defoaming agent is n-octanol.

[0058] In step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 650°C, and the roasting time is 4 hours. After the roasting is completed, it is cooled with the furnace. During the roasting and cooling process, the oxygen content is ensured to be not less than 12%. In step 3, the ambient temperature of the operating room is 15°C, the speed of the mixer is 20rpm, and the mixing time is 6 hours. In step 4, the ambient temperature of the operating room is 15°C, the stirring speed is 500rpm, and the stirring time is 10min. In step 5, the ambient temperature of the operating room is 15°C. After all the back layer powder is added, the stirring speed is increased to 800rpm, and the stirring time is 4 hours.

[0059] Embodiment three:

[0060] According to another preferred embodiment of the ceramic shell backing layer slurry with good fluidity and the preparation method thereof of the present invention, the material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0061] The ceramic shell back layer slurry is a mullite powder back layer slurry, and the mass percentage of each substance in the mullite powder back layer slurry is 77wt% of the back layer powder, 22wt% of silica sol, 0.6wt% of the wetting agent, and 0.4wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 97.8wt% of mullite powder, 1.2wt% of primary spherical mullite sand, 0.6wt% of secondary spherical mullite sand, and 0.4wt% of tertiary spherical mullite sand. The particle sizes of the mullite powder, the primary spherical mullite sand, the secondary spherical mullite sand, and the tertiary spherical mullite sand are 200 mesh, 100 mesh, 120 mesh, and 150 mesh, respectively. The wetting agent is fatty alcohol polyoxyethylene ether; and the defoaming agent is n-octanol.

[0062] In step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 800°C, and the roasting time is 2h. After roasting, they are cooled with the furnace. During the roasting and cooling process, the oxygen content is ensured to be not less than 12%. In step 3, the ambient temperature of the operating room is 25°C, the speed of the mixer is 60rpm, and the mixing time is 4h. In step 4, the ambient temperature of the operating room is 25°C, the stirring speed is 1000rpm, and the stirring time is 5min. In step 5, the ambient temperature of the operating room is 25°C. After all the back layer powder is added, increase the stirring speed to 1200rpm and stir for 2h.

[0063] Embodiment 4:

[0064] According to another preferred embodiment of the ceramic shell backing layer slurry with good fluidity and the preparation method thereof of the present invention, the material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0065] The ceramic shell back layer slurry is a zircon powder back layer slurry, and the mass percentage of each substance in the zircon powder back layer slurry is 80wt% of the back layer powder, 19wt% of silica sol, 0.5wt% of the wetting agent, and 0.5wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 98.4wt% of zircon powder, 0.4wt% of primary spherical zircon sand, 0.6wt% of secondary spherical zircon sand, and 0.6wt% of tertiary spherical zircon sand; the particle sizes of the zircon powder, the primary spherical zircon sand, the secondary spherical zircon sand, and the tertiary spherical zircon sand are 200 mesh, 120 mesh, 140 mesh, and 150 mesh, respectively. The wetting agent is a fatty phosphate; and the defoaming agent is polydimethylsiloxane.

[0066] In step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 680°C, and the roasting time is 2.5 hours. After roasting, they are cooled with the furnace. During the roasting and cooling process, the oxygen content is ensured to be not less than 12%. In step 3, the ambient temperature of the operating room is 18°C, the speed of the mixer is 30rpm, and the mixing time is 4.5h. In step 4, the ambient temperature of the operating room is 18°C, the stirring speed is 650rpm, and the stirring time is 6.5min. In step 5, the ambient temperature of the operating room is 18°C. After all the back layer powder is added, the stirring speed is increased to 900rpm, and the stirring time is 2.5h.

[0067] Embodiment five:

[0068] According to another preferred embodiment of the ceramic shell backing layer slurry with good fluidity and the preparation method thereof of the present invention, the material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0069] The ceramic shell back layer slurry is a zircon powder back layer slurry, and the mass percentage of each substance in the zircon powder back layer slurry is 75.6wt% of the back layer powder, 24wt% of the silica sol, 0.2wt% of the wetting agent, and 0.2wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 98.4wt% of the zircon powder, 0.4wt% of the primary spherical zircon sand, 0.6wt% of the secondary spherical zircon sand, and 0.6wt% of the tertiary spherical zircon sand; the particle sizes of the zircon powder, the primary spherical zircon sand, the secondary spherical zircon sand, and the tertiary spherical zircon sand are 200 mesh, 120 mesh, 140 mesh, and 150 mesh, respectively. The wetting agent is a fatty phosphate; and the defoaming agent is polydimethylsiloxane.

[0070] In step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 760°C, and the roasting time is 3.5 hours. After roasting, they are cooled with the furnace. During the roasting and cooling process, the oxygen content is ensured to be not less than 12%. In step 3, the ambient temperature of the operating room is 22°C, the speed of the mixer is 50rpm, and the mixing time is 5.5h. In step 4, the ambient temperature of the operating room is 22°C, the stirring speed is 900rpm, and the stirring time is 9min. In step 5, the ambient temperature of the operating room is 22°C. After all the back layer powder is added, increase the stirring speed to 1100rpm and the stirring time is 3.5h.

[0071] Embodiment six:

[0072] According to another preferred embodiment of the ceramic shell backing layer slurry with good fluidity and the preparation method thereof of the present invention, the material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0073] The ceramic shell back layer slurry is a zircon powder back layer slurry, and the mass percentage of each substance in the zircon powder back layer slurry is 84wt% of the back layer powder, 15.2wt% of silica sol, 0.4wt% of the wetting agent, and 0.4wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 98.4wt% of zircon powder, 0.4wt% of primary spherical zircon sand, 0.6wt% of secondary spherical zircon sand, and 0.6wt% of tertiary spherical zircon sand; the particle sizes of the zircon powder, the primary spherical zircon sand, the secondary spherical zircon sand, and the tertiary spherical zircon sand are 200 mesh, 120 mesh, 140 mesh, and 150 mesh, respectively. The wetting agent is a fatty phosphate; and the defoaming agent is polydimethylsiloxane.

[0074] In step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 720°C, and the roasting time is 3 hours. After the roasting is completed, it is cooled with the furnace. During the roasting and cooling process, the oxygen content is ensured to be not less than 12%. In step 3, the ambient temperature of the operating room is 20°C, the speed of the mixer is 40rpm, and the mixing time is 5h. In step 4, the ambient temperature of the operating room is 20°C, the stirring speed is 800rpm, and the stirring time is 8min. In step 5, the ambient temperature of the operating room is 20°C. After all the back layer powder is added, the stirring speed is increased to 1000rpm, and the stirring time is 3h.

[0075] Embodiment seven:

[0076] According to another preferred embodiment of the ceramic shell backing layer slurry with good fluidity and the preparation method thereof of the present invention, the material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0077] The ceramic shell back layer slurry is an alumina powder back layer slurry, and the mass percentage of each substance in the alumina powder back layer slurry is 76wt% of the back layer powder, 23wt% of silica sol, 0.5wt% of the wetting agent, and 0.5wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 97.9wt% of the alumina powder, 1.0wt% of the first-level spherical alumina sand, 0.5wt% of the second-level spherical alumina sand, and 0.6wt% of the third-level spherical alumina sand; the particle sizes of the alumina powder, the first-level spherical alumina sand, the second-level spherical alumina sand, and the third-level spherical alumina sand are 325 mesh, 100 mesh, 120 mesh, and 140 mesh, respectively. The wetting agent is fatty alcohol polyoxyethylene ether; and the defoaming agent is n-octanol.

[0078] In step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 720°C, and the roasting time is 3 hours. After the roasting is completed, it is cooled with the furnace. During the roasting and cooling process, the oxygen content is ensured to be not less than 12%. In step 3, the ambient temperature of the operating room is 20°C, the speed of the mixer is 40rpm, and the mixing time is 5h. In step 4, the ambient temperature of the operating room is 20°C, the stirring speed is 800rpm, and the stirring time is 8min. In step 5, the ambient temperature of the operating room is 20°C. After all the back layer powder is added, the stirring speed is increased to 1000rpm, and the stirring time is 3h.

[0079] Embodiment eight:

[0080] According to another preferred embodiment of the ceramic shell backing layer slurry with good fluidity and the preparation method thereof of the present invention, the material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0081] The ceramic shell back layer slurry is an alumina powder back layer slurry, and the mass percentage of each substance in the alumina powder back layer slurry is 72.6wt% of the back layer powder, 27wt% of the silica sol, 0.2wt% of the wetting agent, and 0.2wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 97.9wt% of the alumina powder, 1.0wt% of the first-level spherical alumina sand, 0.5wt% of the second-level spherical alumina sand, and 0.6wt% of the third-level spherical alumina sand; the particle sizes of the alumina powder, the first-level spherical alumina sand, the second-level spherical alumina sand, and the third-level spherical alumina sand are 325 mesh, 100 mesh, 120 mesh, and 140 mesh, respectively. The wetting agent is fatty alcohol polyoxyethylene ether; and the defoaming agent is n-octanol.

[0082] In step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 760°C, and the roasting time is 3.5 hours. After roasting, they are cooled with the furnace. During the roasting and cooling process, the oxygen content is ensured to be not less than 12%. In step 3, the ambient temperature of the operating room is 22°C, the speed of the mixer is 50rpm, and the mixing time is 5.5h. In step 4, the ambient temperature of the operating room is 22°C, the stirring speed is 900rpm, and the stirring time is 9min. In step 5, the ambient temperature of the operating room is 22°C. After all the back layer powder is added, increase the stirring speed to 1100rpm and the stirring time is 3.5h.

[0083] Embodiment nine:

[0084] According to another preferred embodiment of the ceramic shell backing layer slurry with good fluidity and the preparation method thereof of the present invention, the material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0085] The ceramic shell back layer slurry is an alumina powder back layer slurry, and the mass percentage of each substance in the alumina powder back layer slurry is 79wt% of the back layer powder, 20.2wt% of silica sol, 0.4wt% of the wetting agent, and 0.4wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 97.9wt% of the alumina powder, 1.0wt% of the first-level spherical alumina sand, 0.5wt% of the second-level spherical alumina sand, and 0.6wt% of the third-level spherical alumina sand; the particle sizes of the alumina powder, the first-level spherical alumina sand, the second-level spherical alumina sand, and the third-level spherical alumina sand are 325 mesh, 100 mesh, 120 mesh, and 140 mesh, respectively. The wetting agent is fatty alcohol polyoxyethylene ether; and the defoaming agent is n-octanol.

[0086] In step 2, the roasting temperature of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand is 680°C, and the roasting time is 2.5 hours. After roasting, they are cooled with the furnace. During the roasting and cooling process, the oxygen content is ensured to be not less than 12%. In step 3, the ambient temperature of the operating room is 18°C, the speed of the mixer is 30rpm, and the mixing time is 4.5h. In step 4, the ambient temperature of the operating room is 18°C, the stirring speed is 650rpm, and the stirring time is 6.5min. In step 5, the ambient temperature of the operating room is 18°C. After all the back layer powder is added, the stirring speed is increased to 900rpm, and the stirring time is 2.5h.

[0087] Comparative Example:

[0088] On the basis of Example 1, the spherical sand is removed, that is, the ceramic shell back layer slurry is a mullite powder back layer slurry, and the mass percentage of each substance in the mullite powder back layer slurry is 73wt% of the back layer powder (i.e., mullite powder), 26wt% of silica sol, 0.5wt% of wetting agent, and 0.5wt% of defoaming agent. The particle size of the mullite powder is 200 meshes, the wetting agent is fatty alcohol polyoxyethylene ether, and the defoaming agent is n-octanol. The preparation process and process parameters of the mullite powder back layer slurry are basically the same as those of Example 1 (excluding the steps of calcining the spherical sand and mixing the spherical sand with the mullite powder).

[0089] The backing slurry of the comparative example is used to prepare a ceramic shell, and the macroscopic thickness of the ceramic shell is as follows: Figure 4 As shown in Figure 2, the internal microstructure of the ceramic shell is as follows: Figure 5 As shown. The standard flow area based on optical detection is 2453mm 2The thickness of the concave part of the ceramic shell is 7.6mm, the thickness of the flat part is 5.3mm, the thickness uniformity index is 1.44, and all fluidity indicators are reduced. Scanning electron microscopy shows that there is no spherical sand in the back layer slurry and the uniformity of the structure is poor.

[0090] Special note: The technical solution of the present invention involves many parameters, and the synergistic effects between the various parameters need to be comprehensively considered to obtain the beneficial effects and significant progress of the present invention. Moreover, the value ranges of the various parameters in the technical solution are obtained after a large number of experiments. For each parameter and the combination of each parameter, the inventor has recorded a large amount of experimental data. Due to space limitations, the specific experimental data will not be disclosed here.

[0091] It is not difficult for those skilled in the art to understand that the ceramic shell back layer slurry with good fluidity and the preparation method thereof of the present invention include any combination of the invention content and the specific implementation method of the above-mentioned invention specification and the various parts shown in the drawings. Due to the limited space and to make the specification concise, the various schemes composed of these combinations are not described one by one. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A ceramic shell backing layer slurry with good fluidity, characterized by: The mass percentage of each substance in the ceramic shell back layer slurry is 65-87wt% for back layer powder, 12-34wt% for silica sol, 0.2-0.8wt% for wetting agent and 0.2-0.8wt% for defoaming agent; the mass percentage of each substance in the back layer powder is 97-98.5wt% for refractory powder, 0.3-1.5wt% for primary spherical sand, 0.4-0.8wt% for secondary spherical sand and 0.3-0.8wt% for tertiary spherical sand; The refractory powder is any one of mullite powder, zircon powder and alumina powder, and the particle size of the refractory powder is 200-325 mesh; According to the material type of the refractory powder used in the ceramic shell back layer slurry, spherical sand with the same chemical composition is selected, that is, the material of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand are all the same as the material of the refractory powder; the particle size of the first-level spherical sand is 100-120 mesh, the particle size of the second-level spherical sand is 120-140 mesh, and the particle size of the third-level spherical sand is 140-150 mesh; the sphericity values ​​of the first-level spherical sand, the second-level spherical sand, and the third-level spherical sand are not less than 0.95; The method for preparing a ceramic shell back layer slurry with good fluidity comprises the following steps in order: Step 1: according to the designed raw material ratio, weigh refractory powder, first-grade spherical sand, second-grade spherical sand, third-grade spherical sand, silica sol, wetting agent and defoaming agent for use; Step 2: Put the first-level spherical sand, the second-level spherical sand and the third-level spherical sand into a refractory mortar and mix them evenly, then put the refractory mortar containing the first-level spherical sand, the second-level spherical sand and the third-level spherical sand into a roasting furnace for roasting, and cool the roasted first-level spherical sand, the second-level spherical sand and the third-level spherical sand for standby use; Step 3: Put the refractory powder and the cooled first-grade spherical sand, second-grade spherical sand and third-grade spherical sand into a V-type mixer for mixing, and after the mixing is completed, the back layer powder is obtained; Step 4: Add silica sol, wetting agent and defoaming agent into the slurry mixing barrel in sequence, and start the agitator for stirring at the same time; Step 5: While keeping the agitator in the starting state and without changing the stirring speed, add the obtained back layer powder into the slurry mixing barrel and continue to stir; after all the back layer powder is added, start the circulating cooling system of the slurry mixing barrel, and at the same time increase the stirring speed and continue to stir, after the stirring is completed, the ceramic shell back layer slurry with good fluidity is obtained; In step 2, the first-grade spherical sand, the second-grade spherical sand, and the third-grade spherical sand are calcined at a temperature of 650-800°C and a calcination time of 2-4 hours. After calcination, the spherical sand is cooled with the furnace. During the calcination and cooling process, the oxygen content is ensured to be not less than 12%; In step 3, the ambient temperature of the operating room is 15-25°C, the speed of the mixer is 20-60rpm, and the mixing time is 4-6h; In step 4, the ambient temperature of the operating room is 15-25°C, the stirring speed is 500-1000 rpm, and the stirring time is 5-10 min; In step 5, the ambient temperature of the operating room is 15-25°C. After all the backing layer powder is added, the stirring speed is increased to 800-1200 rpm and the stirring time is 2-4 hours.

2. The ceramic shell back layer slurry with good fluidity according to claim 1, characterized in that: The wetting agent is fatty phosphate and / or fatty alcohol polyoxyethylene ether; the defoaming agent is any one of n-octanol, polydimethylsiloxane and polyether defoaming agent.

3. The ceramic shell back layer slurry with good fluidity according to claim 2, characterized in that: The ceramic shell back layer slurry includes mullite powder back layer slurry, zircon powder back layer slurry, and alumina powder back layer slurry; The mass percentage of each substance in the mullite powder back layer slurry is 68-77wt% for the back layer powder, 22-31wt% for the silica sol, 0.3-0.6wt% for the wetting agent, and 0.3-0.6wt% for the defoaming agent; the mass percentage of each substance in the back layer powder is 97.8wt% for the mullite powder, 1.2wt% for the primary spherical mullite sand, 0.6wt% for the secondary spherical mullite sand, and 0.4wt% for the tertiary spherical mullite sand; the particle sizes of the mullite powder, the primary spherical mullite sand, the secondary spherical mullite sand, and the tertiary spherical mullite sand are 200 mesh, 100 mesh, 120 mesh, and 150 mesh, respectively; The mass percentage of each substance in the zircon powder back layer slurry is 75-84wt% of the back layer powder, 15-24wt% of the silica sol, 0.2-0.5wt% of the wetting agent, and 0.2-0.5wt% of the defoaming agent; the mass percentage of each substance in the back layer powder is 98.4wt% of the zircon powder, 0.4wt% of the primary spherical zircon sand, 0.6wt% of the secondary spherical zircon sand, and 0.6wt% of the tertiary spherical zircon sand; the particle sizes of the zircon powder, the primary spherical zircon sand, the secondary spherical zircon sand, and the tertiary spherical zircon sand are 200 mesh, 120 mesh, 140 mesh, and 150 mesh, respectively; The mass percentage of each substance in the alumina powder back layer slurry is 72-79wt% for the back layer powder, 20-27wt% for the silica sol, 0.2-0.5wt% for the wetting agent, and 0.2-0.5wt% for the defoaming agent; the mass percentage of each substance in the back layer powder is 97.9wt% for the alumina powder, 1.0wt% for the primary spherical alumina sand, 0.5wt% for the secondary spherical alumina sand, and 0.6wt% for the tertiary spherical alumina sand; the particle sizes of the alumina powder, the primary spherical alumina sand, the secondary spherical alumina sand, and the tertiary spherical alumina sand are 325 mesh, 100 mesh, 120 mesh, and 140 mesh, respectively.

4. The ceramic shell back layer slurry with good fluidity according to claim 3, characterized in that: The primary spherical zircon sand, the secondary spherical zircon sand and the tertiary spherical zircon sand are prepared by a calcination process, and the calcination temperature is not lower than 1200°C; the primary spherical mullite sand, the secondary spherical mullite sand and the tertiary spherical mullite sand are prepared by a high-temperature melting granulation process, and the melting temperature is not lower than 2000°C; the primary spherical alumina sand, the secondary spherical alumina sand and the tertiary spherical alumina sand are prepared by a high-temperature melting granulation process, and the melting temperature is not lower than 2000°C.

Citation Information

Patent Citations

  • Polymer modified ceramic shell material as well as preparation method and application thereof

    CN118385441A

  • Preparation method of mullite spherical aggregate reinforced refractory material

    CN106396696A

  • High-stability ceramic shell back layer slurry and preparation method thereof

    CN117303893A